Achados anatomopatológicos de linfonodos obtidos de bovinos de abatedouro: estudo retrospectivo e prospectivo - Carlos Eduardo Bastos Lopes (2023)
Inspection activities in slaughterhouses play a crucial role in the sanitary control of zoonoses and foodborne diseases. Therefore, the aim of this study was to identify and analyze the frequency of lymph node diseases diagnosed in cattle from slaughterhouses for human consumption, in samples sent to the anatomopathological diagnosis service of LFDA-MG, from January 2015 to September 2022. A total of 2,000 samples of lymph nodes were analyzed regarding the origin of the property and the Federal Inspection Service (FIS) responsible for the sending, gender, histopathological diagnosis, affected lymphatic site, concomitantly affected organ and gross interpretation. Time pattern analyzes and thematic maps were used to determine epidemiological distribution patterns of the main diagnoses. Paraffin-embedded tissues from cases of lymphoma were submitted to immunophenotyping with anti-CD3 and anti-CD79a. Frozen or paraffin-embedded tissues from the same cases were used to identify enzootic bovine leukosis retrovirus (EBL) by qPCR, which was also used, along with bacterial isolation, in samples of suspected cases of tuberculosis. The year of 2020 (29.3%) concentrated the highest number of samples, with the months of July (x̄ = 60.5) and November (x̄ = 58) being the most representative periods. Altogether, 37 FIS contributed to the analyses, with emphasis on the states of Minas Gerais and Rio Grande do Sul. A total of 12 states and 428 municipalities hosted the origin properties of the studied cattle. Cases of tuberculosis accounted for 89.3% of the samples. Other diagnoses included neoplasms (3.5%), varied lymphadenopathies (2.8%), idiopathic lymphadenitis (2.3%), actinogranulomas (1%), and cases of EBL (0.9%). B- and T-cell lymphomas accounted for 18 and 11 cases, with a predominance of large B-cell lymphomas and peripheral T-cell lymphomas, respectively. Thoracic lymph nodes were associated with most diagnoses. The sensitivity of histopathology surpassed that of other complementary tests in cases of tuberculosis. Sensitivity and specificity values of macroscopic suspicions for definitive diagnoses of tuberculosis and enzootic leukosis were equally satisfactory. It is concluded that the study of the lymph nodes is a fundamental step in the inspection process and should not be underestimated. The association of histopathology with complementary laboratory techniques is crucial for successful diagnosis, especially in complex cases of great epidemiological, economic and zoosanitary importance, such as enzootic leukosis and tuberculosis.